Related Civil Law Studies To Misbruik Van Omstandigheden On The Issue Of Hospital Refusal Of Economically Weak Patients - Yusriando; Gunarto; Jarot Jati Bagus Suseno; Sri Yuliati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Hospitals are health institutions that are given a mandateby the state to provide health services which are reflectedthrough the role of hospitals in providing excellent medicalservices for all Indonesian people without exception. Thisincludes economically weak communities, in reality thereare many cases of rejection of economically weak patientsby hospitals, this is an act that goes against the mandate ofhealth law policy, including committing acts of abuse inmedical service agreements for patients who want healthservices for economically weak communities based on theprinciple of balance of agreement. This article, which usesdoctrinal research methods, looks at the issue of rejectionof economically weak patients by hospitals as a form ofMisbruik van Omstandigheden in therapeutic agreementswhich were born as agreements from the principles of civillaw and medical service agreement law. Ignorance ofeconomically weak patients - economically weak patientsare often helpless when they experience rejection fromhospitals for illogical reasons. Based on the study of thisarticle, it was found that in terms of medical services foreconomically weak communities, the position oftherapeutic agreements and agreements regardinginformed consent as a commitment to health services foreconomically weak communities is unclear, resulting in astate of bias or misbruik van omstandigheden carried outby hospitals for economically weak patients.